If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1x = 12 + 6x Combine like terms: 5x + -1x = 4x 4x = 12 + 6x Solving 4x = 12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 4x + -6x = 12 + 6x + -6x Combine like terms: 4x + -6x = -2x -2x = 12 + 6x + -6x Combine like terms: 6x + -6x = 0 -2x = 12 + 0 -2x = 12 Divide each side by '-2'. x = -6 Simplifying x = -6
| 9w-2=-1w-22 | | -x-40+4x=26 | | 7v/6=-35 | | 4(x-5)+4(x-5)+3(x+6)+3(x+6)= | | 8y+9y-y-4+1y-4y=36 | | 5n-7=5(n+2)+3 | | A=pt-3p | | 1/2-3=9 | | 9(8-12w)= | | 5(x-3)=-(15-5x) | | -68+4x+3x=114 | | 5x/2=-3x+11 | | 5p-2(4-2p)=19 | | Y=-2+-0.6666666667x | | -3/7w=9 | | 2x-(2-x)=13 | | x=(2m-4)/(1+n) | | 125^-2/3 | | 7x^2+40x+25=0 | | 9x-8x-10=13 | | 9.05=8.2 | | 3[8y+2]=10y+2[7y+3] | | 5/12=6/x | | 9+9-1-2+5m-1-4m=32 | | t*5=54 | | 3x-(5+2x)= | | x+4x-73=72 | | 10/3x2/5 | | 5x+16=2X | | 6x/3-18 | | 3/10(220) | | 2-3t+6+4t-12=9t |